Work engagement, job satisfaction and performance: the role of organizational culture - Juyumaya, Jesús E. (Estudios de Administración, 2018)
The study investigated the relationship between work engagement, job satisfaction and task performance, in the Chilean context. We used a cross-sectional survey design, a convenience sample (n=255) (men=28%, women=72%). The survey used the UWES-9 work engagement scale (Schaufeli, Bakker and Salanova, 2006), the generic job satisfaction scale (Macdonald & MacIntyre, 1997) and the performance task scale (Koopmans et al., 2013). The correlations with SPSS were analyzed. The role of organizational culture in the proposed model was also analyzed theoretically. It was found that work engagement has a strong relationship with job satisfaction, and this variable is positively related to task performance. It is expected that strong organizational cultures will positively influence the relationship between work engagement, job satisfaction and task performance.